Using transfer learning to detect galaxy mergers. Issue 1 (28th May 2018) - Ackermann, Sandro; Schawinski, Kevin; Zhang, Ce; Weigel, Anna K; Turp, M Dennis
ABSTRACT: We investigate the use of deep convolutional neural networks (deep CNNs) for automatic visual detection of galaxy mergers. Moreover, we investigate the use of transfer learning in conjunction with CNNs by retraining networks first trained on pictures of everyday objects. We test the hypothesis that transfer learning is useful for improving classification performance for small training sets. This would make transfer learning useful for finding rare objects in astronomical imaging data sets. We find that these deep learning methods perform significantly better than current state-of-the-art merger detection methods based on non-parametric systems such as CAS and GM20 . Our method is end-to-end and robust to image noise and distortions; it can be applied directly without image preprocessing. We also find that transfer learning can act as a regularizer in some cases, leading to better overall classification accuracy ( p = 0.02). Transfer learning on our full training set leads to a lowered error rate from 0.038 ± 1 to 0.032 ± 1, a relative improvement of 15 per cent. Finally, we perform a basic sanity-check by creating a merger sample with our method, and comparing with an already existing, manually created merger catalogue in terms of colour–mass distribution and stellar mass function.